Blood and lymphatic vessel invasion in pT1 colorectal cancer: an international concordance study. Issue 8 (30th April 2015) - Kojima, Motohiro; Puppa, Giacomo; Kirsch, Richard; Basturk, Olca; Frankel, Wendy L; Vieth, Michael; Lugli, Alessandro; Sheahan, Kieran; Yeh, Matthew; Lauwers, Greg Y; Risio, Mauro; Shimazaki, Hideyuki; et al.
Abstract : Aim: This study was performed to evaluate the concordance in pathological assessments of blood and lymphatic vessel invasion (BLI) in pT1 colorectal cancers and to assess the effect of diagnostic criterion on consistency in the assessment of BLI. Methods: Forty consecutive patients undergoing surgical resection of pT1 colorectal cancers were entered into this study. H&E-stained, D2-40-stained and elastica-stained slides from the tumours were examined by 18 pathologists from seven countries. The 40 cases were divided into two cohorts with 20 cases each. In cohort 1, pathologists diagnosed BLI using criteria familiar to them; all Japanese pathologists used a criterion of BLI from the Japanese Society for Cancer of the Colon and Rectum (JSCCR). In cohort 2, all pathologists used the JSCCR diagnostic criterion. Results: In cohort 1, diagnostic concordance was moderate in the US/Canadian and European pathologists. There were no differences in the consistency compared with results for Japanese pathologists, and no improvement in the diagnostic concordance was found for using the JSCCR criterion. However, in cohort 2, the JSCCR criterion decreased the consistency of BLI diagnosis in the US/Canadian and European pathologists. The level of decreased consistency in the assessment of BLI was different between the US/Canadian and European pathologists. Conclusions: A uniform criterion strongly influences the diagnostic consistency of BLI but may not always improve the concordance. Further study is required to achieve an objective diagnosis of BLI in colorectal cancer. The varying effects of diagnostic criterion on the pathologists from Japan, the USA/Canada and Europe might reflect varied interpretations of the criterion. Internationally accepted criterion should be developed by participants from around the world.